2021
DOI: 10.3390/brainsci11020154
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Alcohol Exposure and the Facial Phenotype in Adolescents: A Study Based on Meconium Ethyl Glucuronide

Abstract: Here, we explore the effects of prenatal alcohol exposure (PAE) in adolescence. We investigated associations between meconium ethyl glucoronide (EtG) and facial malformation. For 129 children (66/63 male/female; M = 13.3, SD = 0.32, 12–14 years), PAE was implemented by newborn meconium EtG and maternal self-reports during the third trimester. Cognitive development was operationalized by standardized scores (WISC V). The EtG cut-off values were set at ≥10 ng/g (n = 32, 24.8% EtG10+) and ≥112 ng/g (n = 20, 15.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Prematurity, growth retardation, weight affectation, short palpebral fissures, eyes and upper limbs affectation and attention problems are highlighted in FAS profile compared to non-FASD, being part of the specific diagnosis (Hoyme et al, 2016 ; Wang et al, 2020 ). These findings also confirm previous studies from Maschke et al ( 2021 ) that observed facial abnormalities correlate with child's cognitive performance in FRI and WMI in FASD patients. pFAS profile exhibits distinctions from full FAS, particularly in growth problems and physical traits like microcephaly and upper limb impairment, since pFAS does not meet all the requirements of full FAS (Hoyme et al, 2016 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Prematurity, growth retardation, weight affectation, short palpebral fissures, eyes and upper limbs affectation and attention problems are highlighted in FAS profile compared to non-FASD, being part of the specific diagnosis (Hoyme et al, 2016 ; Wang et al, 2020 ). These findings also confirm previous studies from Maschke et al ( 2021 ) that observed facial abnormalities correlate with child's cognitive performance in FRI and WMI in FASD patients. pFAS profile exhibits distinctions from full FAS, particularly in growth problems and physical traits like microcephaly and upper limb impairment, since pFAS does not meet all the requirements of full FAS (Hoyme et al, 2016 ).…”
Section: Discussionsupporting
confidence: 92%
“…The ML algorithm that best predicted FAS was XGB and the most important features were traditional physical traits, such as height and weight affectations. Additionally, neuropsychological variables, including FRI, internalizing problems and total problems, play a crucial role in the prediction of FAS, and have previously mentioned its association with FASD (Fagerlund et al, 2011 ; Popova et al, 2019 ; Maschke et al, 2021 ). Furthermore, studies with autism and ADHD found that internalizing problems are also increased, leading to long-term anxiety behavior in adulthood (So et al, 2021 ; Andersen et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The participating women did not differ from the non-participating women in marital status [ χ 2 (1) = 0.16, p = 0.690], educational level [ χ 2 (1) = 0.08, p = 0.774], or family income [ χ 2 (2) = 0.97, p = 0.616] at time of childbirth (FRAMES). Mothers and children participating in FRANCES I were contacted again from 2019 to 2021 to take part in the second follow-up wave, FRANCES II ( 46 ). Of the 245 contacted families, 186 (75.9%) with n = 188 children (due to two pairs of twins) agreed to participate again (child age: M = 13.3, SD = 0.34, range 12.8–14.4), of which 167 children (89.8%) participated in person (two 2-h data collection sessions on two different days, including physical examination, neuropsychological testing, interview, questionnaires, and biomarker sample collection) and 21 children (10.2%) only filled out questionnaires by post.…”
Section: Methodsmentioning
confidence: 99%
“…Prenatal alcohol exposure (PAE) is a known risk factor for adverse fetal and child development [ 1 ], potentially leading to a spectrum of maladaptive outcomes, clustered under the term fetal alcohol spectrum disorders [FASD; 2]. Its most severe outcome is fetal alcohol syndrome (FAS), a clinical disorder often diagnosed through physical examination, e.g., of facial features [ 2 , 3 ]. Epidemiological assessment of FAS and FASD is a complex topic and prevalence rates vary depending on region and assessment method, with, e.g., 6 to 9 per 1000 children (FAS) and 24–48 per 1000 children in a representative community in Midwestern US being affected [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to address these problems, ethyl glucuronide (EtG), a biomarker for PAE, has been used to assess both low and medium levels of PAE in previous studies [ 3 , 19 , 26 28 ]. EtG is an ethanol metabolite which can be analyzed through the meconium (first stool of the child), reflecting primarily PAE during the third trimester of pregnancy.…”
Section: Introductionmentioning
confidence: 99%